A 31-YEAR-OLD MAN WITH GRAVES’ DISEASE, EVAN’S SYNDROME AND IMPAIRED LIVER FUNCTION - Hudayani, Ika; Nurfathanah; Umar, Husaini; Aman, Andi Makbul; Sanusi, Himawan; Adam, Fabiola M. S.; Parewangi, A. M. Luthf; Saleh, Sahyuddin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Graves' disease (GD) is an autoimmune disease of the thyroid gland and is the most prevalent cause of hyperthyroidism. Autoimmune hemolytic anemia (AIHA) in GD can appear alone or together with Immune thrombocytopenic purpura (ITP), as part of Evan's syndrome (ES). We report a case of Graves' Disease with Evan's Syndrome and Impaired Liver Function. A 31-year-old male was admitted due to weakness, palpitations, jaundice, and weight loss. Graves’ disease was diagnosed based on existing clinical manifestations, with a total Wayne Index score of 26, elevated FT4, decreased TSH, and positive Thyrotropin Receptor Antibody (TRAb). ES in this patient was based on laboratory results of anemia, thrombocytopenia, reticulocytosis, hyperbilirubinemia, and positive direct antiglobulin test (DAT). The patient was considered to have secondary, rather than primary ES because it was suspected to be caused by GD as an autoimmune disease. He was given thyrozole, propranolol, Kalium Slow Release (KSR), methylprednisolone, and Ursodeoxycholic Acid (UDCA) for impaired liver function. In summary, we reported a 31-year-old male with GD, hematological abnormalities, and impaired liver function. The patient was treated for two weeks and with clinical and laboratory improvements after administering antithyroid, steroid, and UDCA therapy